2008
DOI: 10.1016/j.jvs.2008.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of self-expanding nitinol stents stressed in vitro under simulated intravascular conditions

Abstract: Nitinol self-expanding stents undergo both axial and bending deformation when implanted into the superficial femoral and popliteal arteries. Commercially available stents exhibit a variable ability to withstand chronic deformation in vitro, and their response is highly dependent on the type of deformation applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 31 publications
(43 reference statements)
1
105
0
1
Order By: Relevance
“…[19][20][21] The lack of broad acceptance for PA stent placement is mainly attributable to the fear of stent fractures, with possible subsequent restenosis in this vascular bed with high biomechanical stress next to the knee joint. 7,9,16,22,23 Published data support assumptions that stent design and technical aspects during stent deployment (eg, stent elongation, stent overlap) play major roles in the appearance of stent fractures. 6,8,9 However, the incidence of fractures in second-generation stents was low and ranged between 0% and 8.1% during a 1-year follow-up.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[19][20][21] The lack of broad acceptance for PA stent placement is mainly attributable to the fear of stent fractures, with possible subsequent restenosis in this vascular bed with high biomechanical stress next to the knee joint. 7,9,16,22,23 Published data support assumptions that stent design and technical aspects during stent deployment (eg, stent elongation, stent overlap) play major roles in the appearance of stent fractures. 6,8,9 However, the incidence of fractures in second-generation stents was low and ranged between 0% and 8.1% during a 1-year follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…7,9,16,22,23 Published data support assumptions that stent design and technical aspects during stent deployment (eg, stent elongation, stent overlap) play major roles in the appearance of stent fractures. 6,8,9 However, the incidence of fractures in second-generation stents was low and ranged between 0% and 8.1% during a 1-year follow-up. 6,13,17,24,25 Whether the stent fracture rate in the PA location might increase with longer duration of follow-up is not yet known and should be studied separately.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Both the artery and the stent undergo complex three-dimensional deformations, which over time lead to device fatigue and stent fracturing, and to the artery wall tissue stimulation and in-stent restenosis. For example, using planar radiography on human cadaver models, Nikanorov and his colleagues determined axial strains (from 3% to 23% for various locations) for stented and unstented SFA at 70°/20° and 90°/90° knee/hip flexion [3]. Using static in vivo MRI of the SFA, Cheng and his colleagues measured significant shortening (13% ± 11%) and twisting (60% ± 34%) of unstented SFA between supine and fetal positions [4].…”
Section: Introductionmentioning
confidence: 99%
“…); unfortunately it has been observed that many of these stents implanted in peripheral vessels are fractured [3]- [4]. Currently, several peripheral stent designs are available on a dedicated, fast-growing market exhibiting a variable ability to withstand chronic deformation depending on stent design and the type of applied deformation [5], moreover many stent designs are designed only to survive under a standard pulsatile fatigue environment. Numerical simulations have shown to be a very useful tool in the investigation and optimization of stent design [6]- [7] and to provide novel insights on fatigue/fracture mechanics [8].…”
Section: Introductionmentioning
confidence: 99%